2014
DOI: 10.1007/s00701-014-2088-7
|View full text |Cite
|
Sign up to set email alerts
|

Changes in number of water-filled vesicles of choroid plexus in early and late phase of experimental rabbit subarachnoid hemorrhage model; the role of petrous ganglion of glossopharyngeal nerve

Abstract: We studied the relationship between petrous ganglion cells of the GPN and water vesicles of CP in the early and late phases of SAH, and found that CP vesicles are increased in the early phase of SAH due to irritation of GPN, and decreased in the late phase due to ischemic insult of the petrous ganglion and parasympathetic innervation of the CP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 28 publications
0
36
0
Order By: Relevance
“…Hypersecretion of CSF may also be induced by stimulation of glossopharyngeal and vagus nerve endings that innervate the CP epithelium and arteries. An increase of cytoplasmic water vesicles in the acute phase of SAH is probably due to irritation of both nerves [191][192][193]. Moreover, a recent study suggests that AQP1 may also contribute to hypersecretion of CSF and post-hemorrhagic hydrocephalus.…”
Section: Hemorrhagic Strokementioning
confidence: 99%
See 1 more Smart Citation
“…Hypersecretion of CSF may also be induced by stimulation of glossopharyngeal and vagus nerve endings that innervate the CP epithelium and arteries. An increase of cytoplasmic water vesicles in the acute phase of SAH is probably due to irritation of both nerves [191][192][193]. Moreover, a recent study suggests that AQP1 may also contribute to hypersecretion of CSF and post-hemorrhagic hydrocephalus.…”
Section: Hemorrhagic Strokementioning
confidence: 99%
“…↓ CSF secretion [198] ↑ mRNA for NF-κB, MCP-1, IL1R1, IL-8, IL-6, FAS, TNF-α expression [183] ↑ Iba-1+ and CD68+ epiplexus cells [186] ↑ Number of cytoplasmic water vesicles [191][192][193] ↑ HO-1 expression [183] ↑ AQP1 expression [194] Activation of TLR4 [182] Ischemic Apoptosis or necrosis according to the severity of ischemic injury [201] ↑ ED1+ number, CR3 receptors, expression of MHC I and MHC II antigens [217] ↑ Calcium transfer to CSF [210] Alteration in B-CSF barrier after middle cerebral artery occlusion [207] ↑ Apoptotic cells characterized by nuclear DNA fragmentation after middle cerebral artery occlusion [201] ↑ iNOS expression in epiplexus cells, Number of OX-42+ , ED1+ , OX-18+ , OX-6+ cells in epiplexus position [217] ↑ Permeability of B-CSF barrier for inulin after bilateral carotid occlusion [205] ↑ Expression of TGFβ1, brain-derived neurotrophic factor and other growth factors [216] ↑ MMP-9 expression in infiltrating macrophages [214] ↑ VEGF and eNOS expression [217,218] Plasma membrane and organelle damage; clumping of nuclear chromatin after forebrain ischemia [205,206] ↑ Number of macrophages [220] ↑ CP epithelial cell proliferation Expression of NeuN and GFAP after middle cerebral artery occlusion [215] CP as invasion route for T cells into the ischemic brain [219] Edema, apoptosis of CP epithelial cells after middle cerebral artery occlusion Indistinct epithelial membranes and varying degrees of pyknosis after middle cerebral artery occlusion [214] Desquamation of CP epithelial cells [199] ↓ AQP1 expression up to 24 h ↑ AQP1expression between 24-48 h after global cerebral ischemia [209] ↑ VCAM-1, MAdCAM-1, C3CL1, Nt5e expression [220] Traumatic TBI ↑ Intercellular spaces between CP epithelial cells [225] ↑ Macrophage number in epiplexus position after non-penetrative injury…”
Section: Transporters Othersmentioning
confidence: 99%
“…Aydin et al . showed an important link between petrous ganglion cells and water vesicles of CP were decreased in the late phase of SAH due to ischemic insult of the petrous ganglion network . Acute hydrocephalus is due to vasospasm of choroidal arteries, ependymal cell desquamation and also CSF acidosis …”
Section: Discussionmentioning
confidence: 99%
“…We previously showed that SAH causes cerebral fat embolism because of neurogenic lung edema and lung edema induces decreased blood pH values . CPs produce the most CSF to produce brain temperature …”
Section: Discussionmentioning
confidence: 99%
“…13 At present, neurosurgical practice is confronted by an explosion of technology. [16][17][18] However, our understanding of the mechanisms causing hydrocephalus in NMS is still not clear. A better understanding of the pathophysiology of hydrocephalus in this syndrome will lead to better patient outcome.…”
Section: Discussionmentioning
confidence: 99%